2013
DOI: 10.1007/s10815-013-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Embryo developmental capability and pregnancy outcome are related to the mitochondrial DNA copy number and ooplasmic volume

Abstract: We have shown that blastomere volume is directly proportional to the number of mtDNA copies. Therefore, larger cytoplasmic volume, with earlier cleavage speed, implies more mtDNA copies. Evaluation of mtDNA quantification and the measurement of ooplasmic and blastomere volume may be useful for selection of high quality embryo and pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 50 publications
6
84
2
Order By: Relevance
“…Mitochondrial DNA replication resumes around the time of blastocyst formation and is first observed in trophectoderm (TE) cells (reviewed in St John, 2014), consistent with the significant increase in the energy needs of the embryo associated with rapid cell proliferation and implantation (Van Blerkom, 2011). Mitochondrial replication, in turn, starts after implantation (Murakoshi et al., 2013; Pikó & Taylor, 1987). Mitochondrial DNA copy number is higher in aneuploid blastocysts (which contain an abnormal chromosome number) and in euploid blastocysts that fail to implant (Fragouli et al., 2015), suggesting that higher mtDNA copy number reflects embryonic stress and is associated with lower reproductive potential.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA replication resumes around the time of blastocyst formation and is first observed in trophectoderm (TE) cells (reviewed in St John, 2014), consistent with the significant increase in the energy needs of the embryo associated with rapid cell proliferation and implantation (Van Blerkom, 2011). Mitochondrial replication, in turn, starts after implantation (Murakoshi et al., 2013; Pikó & Taylor, 1987). Mitochondrial DNA copy number is higher in aneuploid blastocysts (which contain an abnormal chromosome number) and in euploid blastocysts that fail to implant (Fragouli et al., 2015), suggesting that higher mtDNA copy number reflects embryonic stress and is associated with lower reproductive potential.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are maternally inherited organelles that serve as the cell's powerhouses, using oxidative phosphorylation to supply ATP. Reproductive age is associated with a decrease in the amount of mitochondrial DNA (mtDNA) [5,6], and decreased mtDNA content leads to poor-quality oocytes and negative fertilization outcomes [7]. However, oocytes themselves cannot be used to predict fertilization outcome owing to ethical concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the mitochondria and mtDNA copy number may be altered during cell differentiation and aging. It has also been reported in previous studies that the alteration of mtDNA participates in the regulation of ovarian function (5)(6)(7)(8). Therefore, it is likely that the dysfunction of the mitochondrion may be associated AA.…”
Section: Introductionmentioning
confidence: 64%
“…In addition, ovarian aging is associated with reduced oocyte mtDNA content and mitochondrial dysfunction (13). Numerous studies have reported that the mtDNA content in the oocytes of aged women or of women with a diminished ovarian reserve is significantly lower when compared with that of young patients or those with a normal ovarian reserve (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation